Pandemic of inequality - Luiza Nassif Pires; Laura de Lima Xavier; Thomas Masterson; Michalis Nikiforos; Fernando Rios-Avila (Levy Economics Institute of Bard College, 2020)
The costs of the COVID-19 pandemic - in terms of both the health risks and economic burdens - will be borne disproportionately by the most vulnerable segments of US society. In this public policy brief, Luiza Nassif-Pires, Laura de Lima Xavier, Thomas Masterson, Michalis Nikiforos, and Fernando Rios-Avila demonstrate that the COVID-19 crisis is likely to widen already-worrisome levels of income, racial, and gender inequality in the United States. Minority and low-income populations are more likely to develop severe infections that can lead to hospitalization and death due to COVID-19; they are also more likely to experience job losses and declines in their well-being. The authors argue that our policy response to the COVID-19 crisis must target these unequally shared burdens - and that a failure to mitigate the regressive impact of the crisis will not only be unjust, it will prolong the pandemic and undermine any ensuing economic recovery efforts. As the authors note, we are in danger of falling victim to a vicious cycle: the pandemic and economic lockdown will worsen inequality; and these inequalities exacerbate the spread of the virus, not to mention further weaken the structure of the US economy.
Keywords: 330